Perceptions of organizational justice and ambivalent sexism: The moderating role of individualism-collectivism - Vaamonde, Juan Diego (Pontificia Universidad Católica del Perú, 2016)
The aim of the present study was to explore the association between perceptions of inter- personal/informational justice and ambivalent sexism among Argentinean employees, and to examine the possible role that collectivism and individualism exert on this association. Participants (128 men and 120 women) completed a battery of instruments to measure the variables of interest. Results showed that perceptions of interpersonal and informational justice were negatively associated with hostile sexism, and that, unexpectedly, perceptions of informational justice were positively associated with benevolent sexism. Vertical collectivism and vertical individualism moderated the relationships between perceptions of interpersonal justice and hostile sexism. Findings are discussed in light of their theoretical and practical implications. Suggestions for future research are provided.